Answer:
Explanation:
Part (A)
From the picture attached,
Line 1 passes through two points (-2, 0) and (-1, 3).
Let the equation of the line is,
y = mx + b
where m = slope of the line
b = y-intercept
Slope of a line passing through
and
is given by,
m =
Therefore, slope of line 1,
m =
m = 3
y-intercept 'b' = 6
Equation of line 1 will be,
y = 3x + 6 --------(1)
Let the equation of line 2 is,
y = m'x + b'
Since line 2 passes through two points (0, -1) and (1, 3)
Slope m' =
= 4
y-intercept b' = -1
Equation of line 2 is,
y = 4x - 1 --------(2)
Part (B)
By equating the values of y from both the equations,
3x + 6 = 4x - 1
4x - 3x = 6 + 1
x = 7
From equation (2),
y = 4(7) - 1
= 28 - 1
= 27